Keterampilan Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Layanan Pembelajaran (Studi Kasus Di SMA Negeri 3 Mukomuko) - Martin, Martin; somantri, Manap; Putri Kartiwi, Asti (Manajer Pendididikan, 2025)
The description of this research are to : 1) Know conceptual skill, 2) human relationship skill, and 3) technical skill of principal in improving the quality of learning services in state Senior High school 3 Mukomuko. The researcher uses a qualitative descriptive research design, with the type of case study research. The source of data in the research are school principal, vice principal for curriculum affairs and teachers. The technique of collecting data are through observation, interviews and documents studies. The technique of analyzing the data that is used in this research has four stages, namely data collection, data reduction, data presentation and the last step is drawing conclusions and verification. The conclusions of this research are : 1) the principal has the concept that quality improvement can be achieved with the support of the right strategy and accuracy in making decisions, in planning work programs. 2). As a leader who is skilled in collaborating with others, the principal has been able to establish good communication, give appreciation to outstanding subordinates, create a comfortable work atmosphere, provide role models to subordinates, provide guidance in carrying out tasks and involve teachers in making various decisions. 3) the principal has been fully responsible for the supervision process and is directly involved in efforts to provide assistance to teachers in classroom management, as a form of technical skill ability.